Problematika Guru dalam Implementasi Proyek Penguatan Profil Pelajar Pancasila (P5) Bertema Bhinneka Tunggal Ika Pada Kurikulum Merdeka Belajar - Ernita, Desi; Ardianto, Ichsan (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to identify and analyze the problems faced by teachers in implementing the Pancasila Student Profile Strengthening Project (P5) with the theme Bhinneka Tunggal Ika at MIN 2 Bengkulu City. The study used a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation. The results of the study showed that teachers faced various obstacles, including limited understanding of the P5 concept, lack of technical training, minimal supporting facilities and infrastructure, and challenges in planning and implementing project modules. In addition, teachers also experienced difficulties in integrating diversity values ​​into contextual learning. These findings provide an important contribution to the development of teacher training strategies, madrasah policies, and strengthening the implementation of the Merdeka Curriculum more effectively and meaningfully, especially in instilling the values ​​of tolerance and diversity from an early age.